NK cell-derived artificial extracellular vesicles elicit potent anti-tumor efficacy and tumor microenvironment reprogramming capability - Xinyue Zhou; Hang Yuan; Xinyue Zhu; Yangli Liu; Jinmin Xiao; Xueting Xie; Linlin Che; Cheng Fang; Chao Yao; Dan Hu; Yufu Zhou; Lixin Wang; et al. (Cancer Nanotechnology)
Abstract Natural Killer cell-derived extracellular vesicles (NK–EVs) hold promise for cancer immunotherapy but face limitations in yield and efficacy. This study developed artificial NK–EVs (NK–aEVs) via extrusion, demonstrating superior scalability and bioactivity compared to natural EVs (NK–nEVs), with enriched cytotoxic proteins (e.g., Granzyme B) and characteristic EV markers (CD63, CD81, TSG101). In vitro, NK–aEVs induced >70% cytotoxicity in lung cancer cells (A549, H1299, H460) at 200 μg/mL, triggered apoptosis, and restored degranulation capacity in cryopreserved NK cells. In murine models, intratumoral NK–aEVs suppressed LLC and MC38 tumor growth by 60% without systemic toxicity. NK–aEVs remodeled the tumor microenvironment by enhancing infiltration of CD8+ T/NK cells while reducing splenic immunosuppressive macrophages and myeloid-derived suppressor cells. Notably, NK–aEVs displayed high biocompatibility and efficacy against NSCLC. This work establishes a scalable platform for EV-based immunotherapy, overcoming production and functional constraints of natural EVs, with translational potential for modulating antitumor immunity.